PHYTOCHEMICAL ANALYSIS, ANTIOXIDANT AND ANTI MICROBIAL ACTIVITY OF WHITE & PINK PSIDIUM GUAJAVA LINNAEUS - C, Deepa Philip; R, Indira Kumari; B, Lavanya (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of the present study was to evaluate phytochemicals, antioxidant and anti microbial activity of white and pink (Guava) Psidium guajava Linnaeus. Methods: Healthy and disease free fresh leaves and fruits of white and pink Psidium guajava Linnaeus were collected and extracted using ethanol and aqueous solvents and their contents were analysed for biological efficacy. Results: The phytochemical analysis of extracts revealed the presence of phenols, glycosides, flavonoids and steroids. The leaf extracts of P. guajava determined by FRP (Ferric reducing power assay) method showed potent antioxidant activity. The antibacterial activity was analysed against five clinically significant organisms by disc diffusion method and leaf extracts of P. guajava Linn, showed maximum zone of inhibition against Pseudomonas aeruginosa, and Klebsiella pneumoniae. The most resistant bacteria were found to be Escherchia coli against P. guajava fruit extract that showed no activity. Conclusion: This study reveals that guava leaf extracts exhibits better phytochemical, antioxidant and antibacterial activity than fruit extracts.